Efektivitas Edukasi Pra-Kateterisasi terhadap Pengetahuan Pasien PJK yang akan Menjalani Tindakan Kateterisasi Jantung - Muliantino, Mulyanti Roberto; Mailani, Fitri; Dafris, Wendo (Universitas Fort De Kock Bukittinggi, 2023)
Background: Cardiac catheterization was a common procedure in the management of patients with coronary heart disease, but this was still unknown among patients. It was impacted on fear, anxiety and high psychological stres when undergoing cardiac catheterization. The aim of this study was to identify the effectiveness of directly pre-catheterization education on increasing the knowledge of inpatients who will undergoing cardiac catheterization. Methods: This was a quasi-experiment with one group pretest-posttest research design. Total 41 patients with coronary heart disease who will undergoing cardiac catheterization participated in this study. Accidental sampling technique was used in this study. The education of pre-catheterization was given for 30 minutes and carried out 1 day before the patients undergoing the procedure. Knowledge of catheterization was measured using a pre-cardiac catheterization knowledge questionnaire. Data were analyzed using paired t-test. Results: The results showed that there was an effect of pre-catheterization education on the knowledge of patients who undergoing cardiac catheterization (p<0.001). Conclusion: Education is effective to increasing patients knowledge before undergoing catheterization and it is important for nurses to provide pre-catheterization education before the procedure in decresing fear, anxiety, stres and make the patients more cooperative.Keywords: education, pre-catheterization, coronary heart disease.